Determinants of continuance intention in mobile commerce usage activities among young consumers. - Azyanee Luqman (2017)
Recent statistics revealed that mobile commerce usage activities were dominated by young consumers from the age group of 20 to 24 years old. Therefore, for the sake of long term growth and profitability, mobile commerce application developers and service providers heavily compete with each other to ascertain the continued usage among the target users. However, the research in the context of post-acceptance environment which focuses on the continuance usage intention, as opposed to pre-acceptance and actual usage of a technology, is still in its early stage. As such, grounded by the Expectation-Confirmation Model (ECM), Technology Acceptance Model (TAM), and Social Cognitive Theory (SCT) framework, the purpose of this study was to examine the continuance intention in mobile commerce usage activities among young consumers by investigating the factors that influence their satisfaction which in turn affect their trust and continuance intention. A total of 632 full time university students from six public universities in the east coast region of Peninsular Malaysia have participated in this study. Data was collected through self-administered survey questionnaires. The partial least squares structural equation modelling (PLS-SEM) method was the main statistical technique employed in this study. The study has shown that habit is found to be the most dominant predictor towards mobile commerce usage activities’ continuance intention, closely followed by innovation attributes and individual characteristics. Whereas, satisfaction is revealed to be predicted by confirmation, innovation attributes, and individual characteristics, respectively. On the other hand, trust is discovered to have neither a significant effect on continuance intention nor a mediating effect on the relationship between satisfaction and continuance intention. Additionally, habit is found to have no moderating effect in the relationship between trust and continuance intention. Overall, the results indicate that the model provides a good understanding of the factors that influence satisfaction and continuance intention in mobile commerce usage activities. Based on the findings, the theoretical and practical implications of the study as well as limitations and recommendations for future research are also discussed.